2004
DOI: 10.1016/j.gca.2004.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of uranyl microprecipitates in subsurface sediments at Hanford Site, USA

Abstract: The dissolution of uranium was investigated from contaminated sediments obtained at the US. Department of Energy (U.S. DOE) Hanford site. The uranium existed in the sediments as uranyl silicate microprecipitates in fractures, cleavages, and cavities within sediment grains. Uranium dissolution was studied in Na, Na-Ca, and NH 4 electrolytes with pH ranging from 7.0 to 9.5 under ambient CO 2 pressure. The rate and extent of uranium dissolution was influenced by uranyl mineral solubility, carbonate concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
163
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(183 citation statements)
references
References 49 publications
18
163
0
2
Order By: Relevance
“…However, because U(VI) release records a coupled dissolution-diffusion process, it is difficult to separate the effects of the individual processes. In this regard, a recent study derived a much higher dissolution rate constant for synthetic Na-boltwoodite (9) than the one obtained in the batch study (8). Errors associated with using a low k should be amplified for the advective regime relative to the SF events.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, because U(VI) release records a coupled dissolution-diffusion process, it is difficult to separate the effects of the individual processes. In this regard, a recent study derived a much higher dissolution rate constant for synthetic Na-boltwoodite (9) than the one obtained in the batch study (8). Errors associated with using a low k should be amplified for the advective regime relative to the SF events.…”
Section: Resultsmentioning
confidence: 88%
“…All other aqueous species were measured (Table 2) and used as input in the model to constrain the dissolution of the intragrain U(VI) phase; the only reaction considered was the dissolution of Na-boltwoodite. All solubility calculations used the same database (19) and activity corrections (the Davies equation) as in the batch study (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic and spectroscopic studies of selected samples from this borehole identified uranyl silicate (uranophane) as the dominant U species, residing within micro fractures of feldspar grains (9)(10)(11)(12)(13). Column and batch experiments using contaminated sediments from this borehole indicated that slow dissolution kinetics of the U(VI) silicates and intragranular mass transfer are expected to keep rates of U(VI) release into pore waters low (14). Laser fluorescence spectroscopy studies of the borehole samples identified UO 2 (CO 3 ) 3 4-and Ca 2 UO 2 (CO 3 ) 3 as the predominant U species in the plume aqueous phase (3).…”
Section: Introductionmentioning
confidence: 99%
“…To access the reactivity of materials for U retention or removal in the laboratory, many operational leaching solutions have been defined (Duff et al 1997, Fredrickson et al 2000, Gadelle et al 2001, Kaplan & Serkiz 2001, Liu et al 2004). All these solutions are more aggressive than natural waters.…”
Section: Effect Of the Leaching Solution: Carbonate Contentmentioning
confidence: 99%